A collection of tools for land restoration - Pingault, N.; Meybeck, A.; Mehmood-Ul-Hassan, M.; Noordwijk, M. van; Minang, Peter A.; Gitz, V. (CGIAR Research Program on Forests, Trees and Agroforestry, 2021)
Forests and trees have a major role to play to advance the 2030 Agenda for sustainable development and address major global challenge such as: climate change, deforestation, forest and land degradation, biodiversity erosion, poverty and food insecurity. Over the last ten years, with the Bonn Challenge, the New York Declaration on Forests, the UN Decade on Ecosystem Restoration, and several regional initiatives, forest and landscape restoration has gained increased traction on the political agenda. Successful and sustainable land restoration implies to consider a wide range of interconnected variables and, thus, requires a broad, diverse and transdisciplinary knowledge, as well as a deep understanding of local socio-ecological contexts. Research and development institutions play a central role in generating the needed knowledge and sharing it with the relevant stakeholders. This is why FTA, the CGIAR research program on forests, trees and agroforestry prepared with its partners this compilation of existing restoration tools developed by CGIAR research programs (CRPs), CGIAR cen ters and partner organizations. This document aims to inform the different stakeholders involved in restoration at different scales (policy makers, forest managers and restoration practitioners, land owners, project managers, conservation organizations, students and researchers) and help them find the tools they need to achieve their specific objectives in a given context.